EVALUASI IMPLEMENTASI PELAPORAN KEUANGAN SEBAGAI BENTUK AKUNTABILITAS ORGANISASI KEAGAMAAN - Maria Kurniati Gedi Raya (Journal of Accounting and Management Innovation, 2017)
The purpose of the research to find out whether the financial reporting that is applied by the Catholic Church of St. Paulus Miki Salatiga has been in accordance with the standards established Archdiocese of Semarang and SFAS 45, 2011. The research method used is descriptive qualitative research analysis method using case studies. The results of this study indicate that the financial statements produced by the Catholic Church of St. Paulus Miki Salatiga was aligned with the standards established Archdiocese of Semarang and SFAS 45, 2011 by presenting the Financial Position Reports, Activity Reports, Cash Flow Statement, and Notes to Financial Statements. However there are differences in the way of adjustment and recording of financial statements made by the Catholic Church of St. Paulus Miki Salatiga against the revised SFAS 45, 2011 in accordance with the characteristics of the parish.Keywords: SFAS 45, financial statements, accountability